Representative Nigerian anthropometric data for automotive applications - Uba, Muhammad Abdulazeez; Abdullah, Kassim Abdulrahman; Faris, Waleed Fekry (Institut Pengurusan Penyelidikan (RMI), Universiti Teknologi MARA, 2018)
An automotive policy is been pursued by the government of Nigeria which is aimed at curtailing the dominance of imported vehicles in the Nigerian automobile market. The policy is designed to cater for the automobile demands of the Nigerian population. Since these vehicles would be produced for the Nigerian population and used by them over a period of time, it is imperative that the vehicles are made for the ideal fit of the target population of the end users. The automotive design practice starts with a deliberation about the proportion and category of the car and how many people that the car would accommodate. The designers take into account the proportions of the occupants and drivers and their position in the vehicle environment to ensure that the appropriate number of users can be accommodated. This study provides a representative anthropometric data of Nigerians as a guide for the ergonomic design of automobiles intended for the Nigerian market. A controlled selection of subjects reflecting the ethnic, age, gender and anthropometric spread of the Nigerian population was conducted. A total of 863 subjects comprising 460 males and 403 females participated in the exercise and 60 body dimensions applicable in automotive design, digital human modelling and vehicle occupant packaging were obtained using standard anthropometric instruments. The subjects were selected from the four major ethnic groups in Nigeria as well as 23 other ethnic groups reflecting the ethnic distribution of the Nigerian population. The data obtained were statistically analysed using Microsoft Excel and SPSS to obtain the necessary percentile values as well as the means and standard deviations. The results obtained were used to propose some recommendations for occupant packaging dimensions for use in the design of vehicles intended for the Nigerian market so as to ensure the safety, comfort and security of the users